1995
DOI: 10.1254/jjp.67.91
|View full text |Cite
|
Sign up to set email alerts
|

Histological Evidence for Neuroprotective Action of Nebracetam on Ischemic Neuronal Injury in the Hippocampus of Stroke-Prone Spontaneously Hypertensive Rats

Abstract: ABSTRACT-Theprotective effect of nebracetam on ischemic neuronal damage was histologically examined in the pyramidal cell layer of the hippocampal CAI subfield 7 days after operation using stroke-prone spontaneously hypertensive rats (SHRSP) subjected to 10-min bilateral carotid occlusion. Nebracetam (50 and 100 mg/kg), given orally 10 min after reperfusion, dose-dependently protected against ischemic delayed neuronal damage in the SHRSP with occlusion; however, the blood pressure remained unchanged following … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

1996
1996
2010
2010

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 11 publications
1
0
0
Order By: Relevance
“…TIR resulted in a large decrease in viable pyramidal cells in SHRSP, which confirmed the previous qualitative studies (Yamashita et al 1994;Nakashima et al 1995;Sakurai-Yamashita et al 2003). The present quantitative study indicated for the first time that the decrease was about a half in average.…”
Section: Discussionsupporting
confidence: 91%
“…TIR resulted in a large decrease in viable pyramidal cells in SHRSP, which confirmed the previous qualitative studies (Yamashita et al 1994;Nakashima et al 1995;Sakurai-Yamashita et al 2003). The present quantitative study indicated for the first time that the decrease was about a half in average.…”
Section: Discussionsupporting
confidence: 91%